2018
DOI: 10.1097/hmr.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

The influence of formal and informal policies and practices on health care innovation implementation: A mixed-methods analysis

Abstract: Informal policies and practices may compensate or substitute for formal policies and practices under certain conditions (e.g., smaller health care organizations). Further research is needed to investigate the role of formal and informal policies and practices in shaping a strong and sustainable implementation climate and subsequent effective innovation implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Examining implementation and/or sustainability without considering the relationship between these processes represents a missed opportunity to consider how the implementation process influences longer-term sustainability of an innovation. When sustainability has been discussed in prior studies, it is often discussed tangentially to implementation (Chuang, 2011;DiMartino et al, 2018); however, our findings indicate that sustainability could stand alone as an explicit theoretical construct within an implementation framework. This is particularly important in the context of grant-funded initiatives, which are not always sustained after grant funding is terminated.…”
Section: Discussionmentioning
confidence: 65%
“…Examining implementation and/or sustainability without considering the relationship between these processes represents a missed opportunity to consider how the implementation process influences longer-term sustainability of an innovation. When sustainability has been discussed in prior studies, it is often discussed tangentially to implementation (Chuang, 2011;DiMartino et al, 2018); however, our findings indicate that sustainability could stand alone as an explicit theoretical construct within an implementation framework. This is particularly important in the context of grant-funded initiatives, which are not always sustained after grant funding is terminated.…”
Section: Discussionmentioning
confidence: 65%
“…Consideration should also focus on accessibility of and proximity to important professional and organizational resources. Third, to promote network high density, champions should be encouraged to focus on team‐building strategies that prioritize team cohesion, trust and collaboration (DiMartino et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Third, to promote network high density, champions should be encouraged to focus on team-building strategies that prioritize team cohesion, trust and collaboration (DiMartino et al, 2018).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…To sum up, prior service research has identified on a conceptual level new service provider roles that emerge in light of the increase in technology use in services (Bowen, 2016; Larivière et al , 2017). The value of informal influences on technology innovation in health care is documented (DiMartino et al , 2018); however, prior research also suggests that work context shapes organizational role enactment (Dierdorff et al , 2009). The implication is that new roles are enacted at and affect different levels within the organization.…”
Section: Literature Reviewmentioning
confidence: 99%